Early versus delayed enteral nutrition in ICU patients with sepsis: a propensity score-matched analysis based on the MIMIC-IV database - Xu, Fuchao; Xu, Jianxin; Ma, Jinjin; Xu, Wenbo; Gu, Shuangshuang; Lu, Geng; Wang, Jun (Frontiers in Nutrition, 2024)
Background Early enteral nutrition (EN) is recommended for sepsis management, but its optimal timing and clinical benefits remain uncertain. This study evaluates whether early EN improves outcomes compared to delayed EN in patients with sepsis. Methods We analyzed data of septic patients from the MIMIC-IV 2.2 database, focusing on those in the Medical Intensive Care Unit (MICU) and Surgical Intensive Care Unit (SICU). Patients who initiated EN within 3 days were classified into the early EN group, while those who started EN between 3 and 7 days were classified into the delayed EN group. Propensity score matching was used to compare outcomes between the groups. Results Among 1,111 patients, 786 (70.7%) were in the early EN group and 325 (29.3%) were in the delayed EN group. Before propensity score matching, the early EN group demonstrated lower mortality (crude OR = 0.694; 95% CI: 0.514–0.936; p = 0.018) and shorter ICU stays (8.3 [5.2, 12.3] vs. 10.0 [7.5, 14.2] days; p < 0.001). After matching, no significant difference in mortality was observed. However, the early EN group had shorter ICU stays (8.3 [5.2, 12.4] vs. 10.1 [7.5, 14.2] days; p < 0.001) and a lower incidence of AKI stage 3 (49.3% vs. 55.5%; p = 0.030). Subgroup analysis revealed that early EN significantly reduced the 28-day mortality rate in sepsis patients with lactate levels ≤4 mmol/L, with an adjusted odds ratio (aOR) of 0.579 (95% CI: 0.361, 0.930; p = 0.024). Conclusion Early enteral nutrition may not significantly reduce overall mortality in sepsis patients but may shorten ICU stays and decrease the incidence of AKI stage 3. Further research is needed to identify specific patient characteristics that benefit most from early EN.